Modulation of lipid vesicle–membrane interactions by cholesterol. Issue 40 (12th September 2022) - Chng, Choon-Peng; Hsia, K. Jimmy; Huang, Changjin
Abstract : Our systematic molecular dynamics simulations reveal that cholesterol modulates the interaction pathways between a lipid vesicle and a planar membrane by simultaneously regulating membrane stiffness and membrane fusion. Abstract : Nanoscale lipid vesicles are attractive vehicles for drug delivery. Although often considered as soft nanoparticles in terms of mechanical deformability, the fluidic nature of the lipid membrane makes their interactions with another lipid membrane much more complex. Cholesterol is a key molecule that not only effectively stiffens lipid bilayer membranes but also induces membrane fusion. As such, how cholesterol modulates lipid vesicle–membrane interactions during endocytosis remains elusive. Through systematic molecular dynamics simulations, we find that membrane stiffening upon incorporating cholesterol reduces vesicle wrapping by a planar membrane, hindering endocytosis. Membrane fusion is also accelerated when either the vesicle or the planar membrane is cholesterol-rich, but fusion becomes minimal when both the vesicle and planar membrane are cholesterol-rich. This study provides insights into vesicle–membrane interactions in the presence of cholesterol and enlightens how cholesterol may be used to direct the cellular uptake pathways of nanoliposomes.